Lifelong Learning as a Holistic Paradigm: A Conceptual Analysis of Dimensions, Characteristics, and Systemic Implications - Sahroni Sahroni; Muslihin Muslihin; Suhadi Suhadi (Edumaspul: Jurnal Pendidikan, 2025)
This article examines Lifelong Learning as a response to technological disruption and sustainable development demands. Through systematic literature review of credible sources, this study identifies its main characteristics: learning continuity, integration of educational pathways, flexibility, self-directed learning, and inclusivity. The findings reveal this paradigm has multidimensional impacts covering individual development, social cohesion, economic enhancement, cultural preservation, and participatory citizenship. Its implementation requires systemic transformation through competency-based curriculum reform, recognition of non-formal learning (RPL), digital technology utilization, and multi-stakeholder collaboration. The study concludes that Lifelong Learning is a social imperative for creating an adaptive and globally competitive learning society. Recommendations include developing national qualification frameworks, digital infrastructure equity, and sustainable funding.